Escape to You (Montana heat, 2, 1, 2017)
"He discovered her during a Montana blizzard, freezing cold, impossibly vulnerable, a little boy by her side. Undercover DEA Agent Beck "Trigger" Cooke is astonished to recognize Ashley Swan- award-winning actress, famous beauty... and missing for over a year. To keep her and the child hidden from a sadistic madman, he secrets the pair away to his isolated home. No longer a prisoner, and protected at Hope Ranch, Ashley recovers and learns the tall, tempting federal agent may have a dark past, but it hasn't destroyed his sense of honor. As they shed past roles and find common ground, Ashley and Trigger can't help but fall slowly, carefully, in love. But danger still lurks ouside the boundaries of Hope Ranch, for until her crazed captor is brought to justice, and Trigger's undercover past is laid to rest, none of them will ever be truly safe..." Provided by publisher.

Escape to you (#1): Montana Heat (Montana heat, 2, 1, 2017)
"He discovered her during a Montana blizzard, freezing cold, impossibly vulnerable, a little boy by her side. Undercover DEA Agent Beck "Trigger" Cooke is astonished to recognize Ashley Swan- award-winning actress, famous beauty... and missing for over a year. To keep her and the child hidden from a sadistic madman, he secrets the pair away to his isolated home. No longer a prisoner, and protected at Hope Ranch, Ashley recovers and learns the tall, tempting federal agent may have a dark past, but it hasn't destroyed his sense of honor. As they shed past roles and find common ground, Ashley and Trigger can't help but fall slowly, carefully, in love. But danger still lurks ouside the boundaries of Hope Ranch, for until her crazed captor is brought to justice, and Trigger's undercover past is laid to rest, none of them will ever be truly safe..." --

Protected by love (#0.5): Montana Heat (Montana heat, 1, 1, 2017)
"It was DEA Agent Caden Cooke's third chance to impress beautiful chef Mia Martin. He'd already stood her up twice, and was shocked she was even giving him another chance. For Caden, taking down the bad guys is important, but Mia's made it clear there's no excuse for his bad behavior. So he's vowed to make it worth her while with an apology he's cooked up just for her. From the moment they meet, it's clear this isn't just another fix up. The sparks flying between them are undeniable; the tension is electric. Then, suddenly, the best moments of their lives turn treacherous when a drug dealer set on revenge puts their lives in danger. And Mia and Caden quickly realize they will do anything to protect the other--and live for the love neither of them expected."--Provided by publisher.

Tempted by Love (Montana heat, 4, 1, 2018)
"She was this Montana Man's greatest temptation . . .Alina Cooke--little sister of his two best friends--is the last woman DEA agent Jay Bennett should be waking up next to on the day of her brother's wedding. But their powerful attraction ignited a powder keg of desire, and their once simple friendship has just become impossibly complicated. Alina's always been steady, focused, and lived on the safe side of life. Jay is totally devoted to his dangerous job. She knows a future with him will be filled with worry that one day he won't come home. She's done it with her brothers. She's not sure she can face that uncertainty with the man she loves. Yet being in his arms is a bad idea they keep repeating, again and again. When Alina is run off the road, Jay fears his job has made her a target. But the threat in Alina's life is closer than they think. As the enemy gets more ruthless, Alina proves she is no easy target and Jay will do anything to bring them down. Because surviving and being together is the only thing that matters."--Provided by publisher.

Tempted by love (#3): Montana Heat (Montana heat, ,, 2018)
She was this Montana Man's greatest temptation...Alina Cooke--little sister of his two best friends--is the last woman DEA agent Jay Bennett should be waking up next to on the day of her brother's wedding. But their powerful attraction ignited a powder keg of desire, and their once simple friendship has just become impossibly complicated. Alina's always been steady, focused, and lived on the safe side of life. Jay is totally devoted to his dangerous job. She knows a future with him will be filled with worry that one day he won't come home. She's done it with her brothers. She's not sure she can face that uncertainty with the man she loves. Yet being in his arms is a bad idea they keep repeating, again and again. When Alina is run off the road, Jay fears his job has made her a target. But the threat in Alina's life is closer than they think. As the enemy gets more ruthless, Alina proves she's no easy target and Jay will do anything to bring them down. Because surviving and being together is the only thing that matters.

True to you (Montana heat, 3, 1, 2018)
Undercover DEA Special Agent Dawson King spent five months in a Montana prison establishing a fake identity to take down a ruthless drug dealer and put him behind bars. Except there's a wild card...the killer's beloved daughter. Cara Potter may appear to be on the right side of the law, but King has learned the hard way to trust no one--even someone as tantalizing as the coffer shop owner. She's irresistible...but is she also dangerous?--from Publishers description.

True to you (#2): Montana Heat (Montana heat, 3, 1, 2018)
Undercover DEA Special Agent Dawson King spent five months in a Montana prison establishing a fake identity to take down a ruthless drug dealer and put him behind bars. Except there's a wild card...the killer's beloved daughter. Cara Potter may appear to be on the right side of the law, but King has learned the hard way to trust no one--even someone as tantalizing as the coffer shop owner. She's irresistible...but is she also dangerous?--from Publishers description.